2001
DOI: 10.1051/rnd:2001124
|View full text |Cite
|
Sign up to set email alerts
|

Increase of plasma eCG binding rate after administration of repeated high dose of eCG to cows

Abstract: -Equine chorionic gonadotrophin (eCG) is still used to promote follicular growth in cattle and, more recently with an increased frequency of administration, in ovum pick-up protocols. The aim of this experiment was to verify the possible effect of high frequency of administration on the immune response to eCG. The profiles of eCG binding rate, in the blood of two groups (A, B) of 4 primiparous cross breed beef cows (3-3.5 years old) submitted weekly for 5 to 10 weeks to repeated high doses (1 000-2 000 IU) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
10

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 32 publications
2
14
0
10
Order By: Relevance
“…eCG's effect after repetitive use (revised by DRION et al, 1998;ROY et al, 1999a;DRION et al, 2001). the positive effect of eCG on follicle development has not been completely determined.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…eCG's effect after repetitive use (revised by DRION et al, 1998;ROY et al, 1999a;DRION et al, 2001). the positive effect of eCG on follicle development has not been completely determined.…”
Section: Discussionmentioning
confidence: 99%
“…the eCG administration can increase the concentration of anti-eCG antibodies after the first use (ROY et al, 1999b;MaNtOVaNI, 2010) and some studies have reported an additive effect of subsequent treatments (ROY et al, 1999a;DRION et al, 2001). Furthermore, most studies have concluded that there is an animal individuality to the immune response against eCG (DRION et al, 2001;MaNtOVaNI, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations